Color Perception in Civil Aviation (International Journal of Food and Nutritional Sciences, 2022)
A disorder known as colour vision insufficiency (CVD) makes it impossible for people to tell some colours apart from others. The Aeronautical Commission of the International Civil Air Navigation Authority developed occupational colour vision requirements in aviation in 1919. In the past few years, worries have been raised about the possibility that the aviation industry's present colour vision requirements are both inconsistent globally and overly strict. The tasks that pilots face in the modern aviation environment are not necessarily reflected in the examinations that are used. Due to this misunderstanding, deserving candidates for selection as aircrew may be disqualified.Clinical diagnosis tests are used on the ground by medical personnel to determine whether CVD is compatible with aircraft crew. These medical exams were created especially to identify the type, severity, and existence of CVD. There are currently no clinical tests that quantify operational performance when flying an aeroplane. Clinical tests have been given arbitrary pass scores, and those who fail them will either face operating limitations or be completely disqualified.The required clinical exams and the corresponding passing scores differ significantly amongst regulators.An individual may be excluded in one jurisdiction even though they may not be in another. In order to determine the scope of evidence-based recommendations for the minimal colour vision standards for flight crew as well as for civil aviation in India, this article reviews more recent diagnostic procedures used by various nations for evaluating colour vision.